Modern wound care application in diabetic wound management - Rohmayanti, .; Handayani, Estrin (International Journal of Research in Medical Sciences, 2017)
Diabetes mellitus is a group of metabolic disease which facilitates diabetic wound foot. To prevent long diabetic wound complication and worse condition it is needed wound care for diabetic patient. Modern bandage has been used for recent wound care technique. The principles of modern wound care product are maintaining and watching over the humid environment of the wound to facilitate the wound healing process, maintaining liquid tissue deprivation and cell decease. This research was aimed to find out how modern wound bandage is applied to the diabetic patient and to find out the influence in healing wound phase. This research is qualitative research using phenomenology approach, 4 wound diabetic patients who were hospitalized for 2 weeks using modern wound care method in Magelang regency were participated. The participants were elected using purposive sampling method. Observation and interview were used to obtain data, data was analyzed using explanation building method. The results of this research have 4 topics which are wound examination, type of modern bandage, the way of wound care, and the influence toward the wound. Bates-Jensen Wound was used for the wound examination, the type of bandage used were hydrogel and wound ointment, TIME management approach was used in wound care, and the wound care influences the decreasing of wound size, wound proliferation and granulation. Modern bandage application of diabetic wound influences the decreasing of wound size, wound proliferation and granulation. Paramedic is suggested to use modern wound care method in diabetic wound management.